Computer technology as a factor sistemoobrazuyuschy transition to inclusive education of persons with visual impairment (Pedagogy of Higher and Secondary Education, 2012)
Tulashvili Y. Computer technology as a factor sistemoobrazuyuschy transition to inclusive education of persons with visual impairment.In the article the role of modern information technologies in computer training for people with blindness, as well as their application in the inclusion education of students with disabilities.
Keywords: the disabled student; professional education; blind; information technologies; inclusion in education